(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article covers the issues of correlation between informative and procedural components of pedagogical knowledge in the structure of higher education; its fundamental nature and professional orientation of pedagogical discipline curriculum, modul structures of academic studies and various approaches to future teachers training.